Why Emotion at Work Matters: Examining the Influence of Emotional Labour and Emotional Intelligence on Workplace Behaviours among Service Workers in East Malaysia - Magdalene Ang Chooi Hwa; Hanudin Amin (Kajian Malaysia, 2016)
Using the emotion regulation theory as an analytical framework, this paper investigates the direct effects of emotional labour and emotional intelligence on two workplace behaviours, i.e. organisational citizenship behaviour and deviant workplace behaviour. It also explores how these path linkages could be moderated by emotional intelligence. Data were gathered via survey questionnaires on 205 service employees and their co-workers in East Malaysia. The results show that emotional labour and emotional intelligence significantly influenced the two workplace behaviours in the expected directions. Emotional intelligence was also found to significantly moderate the relationship between emotional labour and deviant behaviour, but not that of emotional labour and organisational citizenship behaviour. Finally, theoretical, managerial and future research implications are included.